An Efficient Cross-Domain Data Transmission Scheme for Wireless Body Area Networks. - Luo, Ming; Hu, Xingtong; Luo, Yi (Journal of Medical Systems, 2020)
Wireless body area networks (WBANs) have become a prospective technology for the next generation healthcare services, in which tiny sensors are placed either on the skin or in the body of human to transmit real-time monitored data to the medical service provider (MSP). In order to protect the transmitted data from leakage, forgery or alteration, constructing a secure data transmission scheme for WBANs that achieves confidentiality, authentication and integrity is necessary. Also, in practical application of WBANs, patient and MSP are in different domain networks in general. In this article, we first design a cross-domain certificateless signcryption (CDCS) scheme, then an efficient cross-domain data transmission scheme for WBANs is proposed based on the new CDCS scheme. The data transmission scheme realizes authentication, confidentiality, anonymity, nonrepudiation, integrity, registration security and KSTI security. Compared to present two security schemes for the WBANs based on certificateless signcryption, our designed scheme entitles patient and MSP to use different cryptographic parameter in different domain networks. Moreover, the new scheme has advantages in communication overhead and computation cost.